STRUCTURAL DESIGN LIQUID BULK DOCK IN CAMPLONG FUEL OIL TERMINAL, EAST JAVA - Pandya Luhur, Akmal
Indonesia is one of the largest archipelagic countries in the world with water area reaching 75%. With Indonesia's geographical condition as an archipelagic country, shipping activities are very important as an inter-island distribution medium, one of which is to the Madura and East Java regions. Thus, to meet the supply and increase the effectiveness of the distribution of fuel to the Madura and East Java regions which previously used Single Point Mooring (SPM), another option is needed, namely the design of a bulk dock facility located at the Camplong Fuel Oil Terminal (TBBM), East Java. This wharf is designed to be able to receive the tanker “MT Kurau” with a capacity of 6500 DWT. This final project discusses the design of the dolphin type liquid bulk dock consisting of a loading platform, breasting dolphin, mooring dolphin, and trestle with structural elements consisting of beams, plates, pile caps, and piles. The initial design or initial design produces the dimensions of the pier and the structural elements of the pier based on the dominant loading on the pier. The dock structure is then modeled using structural software and optimization or changes to the dock structure are carried out to obtain UCR and deflection values that meet the design criteria used. The output of the structural modeling after obtaining the optimum design is the forces in the concrete elements and the bearing reaction of the pier structure. The internal style is used in the next stage, namely the design of the reinforcement of the pier structural elements. Furthermore, the required pile depth calculation for each structure is carried out based on the laying reaction obtained from the structural model and soil condition data at the dock location. The results of this final project are the dimensions of the pier structure and pier structural elements, facilities for berthing and mooring of ships, details of reinforcement for pier structural elements, and the depth of pile driving.